2021
DOI: 10.3233/com-210310
|View full text |Cite
|
Sign up to set email alerts
|

Reverse mathematics and Weihrauch analysis motivated by finite complexity theory

Abstract: We extend a study by Lempp and Hirst of infinite versions of some problems from finite complexity theory, using an intuitionistic version of reverse mathematics and techniques of Weihrauch analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…They address the question of whether there exist graphs for which determining their corresponding supergraph is more intricate. This question was initially posed in [13], where it was observed that for totally disconnected infinite graphs, deciding whether they are supergraphs of given graphs is equivalent to LPO, the simplest discontinuous problem. Cipriani and Pauly confirm the existence of a graph G such that LPO < W IS G while also exploring the complexity of the search problem.…”
Section: Supergraphsmentioning
confidence: 99%
“…They address the question of whether there exist graphs for which determining their corresponding supergraph is more intricate. This question was initially posed in [13], where it was observed that for totally disconnected infinite graphs, deciding whether they are supergraphs of given graphs is equivalent to LPO, the simplest discontinuous problem. Cipriani and Pauly confirm the existence of a graph G such that LPO < W IS G while also exploring the complexity of the search problem.…”
Section: Supergraphsmentioning
confidence: 99%